The Political Transition from the Old Order to the New Order in Indonesia - Aisyah Aura Putri; Bella Insani Hutapea; Kevin Hutagalung; M. Arif Fauzi (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
The transition from the Old Order to the New Order marked a critical turning point in Indonesia’s political history, reshaping the country’s governance structure and state ideology. This study examines the factors driving the transfer of power, the process through which the transition occurred, and its implications for Indonesia’s political development. Employing a qualitative historical approach, the research applies the historical method through the stages of heuristics, source criticism, interpretation, and historiography to reconstruct and analyze the events surrounding the transition. The findings reveal that the transfer of power was precipitated by a convergence of political and economic crises, escalating ideological conflicts, and the aftermath of the 1965 September 30th Movement (G30S), all of which substantially weakened President Sukarno’s authority. The consolidation of military influence and the issuance of the 11 March Order (Supersemar) facilitated the emergence of the New Order under Suharto’s leadership. The study argues that although the transition succeeded in restoring political stability and accelerating economic development, it simultaneously institutionalized centralized political authority and curtailed democratic participation, thereby creating a long-lasting legacy that continues to influence Indonesia’s political landscape.